Socio-Demographic and Employment Dynamics on Indonesia's Economic Growth - Sri Endang Saleh; Boby Rantow Payu (Fakultas Ekonomi Universitas Kadiri, 2026)
This study investigates labor and socio-demographic factors that contribute to regional economic growth in Indonesian provinces between 2020 and 2024. Using a regression analysis of a panel, we assess how several indicators, such as the population growth rate (PGR), proportion of working-age population (WAP), average years of schooling (AYS), labor force participation rate (LFPR), and formal employment (FE), shape regional GDP per capita. We adopted a Fixed Effect Model based on tests from Chow and Hausman. We find a significant negative impact from PGR, whereas significant positive contributions are from AYS and LFPR. However, there is no meaningful difference from zero for WAP and FE. The findings demonstrate a beneficial role of human capital and labor participation in regional broad-based growth.